Morphological change of OLT after excision of osteochondral fragment with microfracture on MRI. Issue 3 (14th September 2018) - Tsuyuguchi, Yusuke; Nakasa, Tomoyuki; Sawa, Mikiya; Yoshikawa, Masahiro; Ota, Yuki; Kanemitsu, Munekazu; Adachi, Nobuo
Category: Ankle Introduction/Purpose: Osteochondral lesion of talus (OLT) is treated by several procedures such as bone marrow stimulation technique, cartilage fragment fixation, or autologous osteochondoral bone implantation. The choice of surgical methods depends on the size of lesion and cartilage condition. For unstable small lesion, excision of osteochondral fragment is usually performed. Good clinical results after this procedure is reported, but it is unclear that the morphological repair of subchondral bone and cartilage like tissue at the lesion. The purpose of this study is to evaluate the restoration of subchondral bone and cartilage like tissue after arthroscopic microfracture with excision of osteochondral fragment, and to investigate the clinical outcomes of this operation for the athletes. Methods: From 2005 to 2015, 11 patients (6 men and 5 women) were performed arthroscopic microfracture with excision of osteochondral fragment for OLT. Average age was 28.6 years old (17 - 59 years old). The site of OLT was 10 medial and 1 lateral. The cases of athletes were 7 of 11 cases. The size of preoperative OLT by MRI, measure the depth of the resected site on 3-month postoperative MRI. And we evaluated the appearance of the repair site on 1 year postoperative MRI, clinical outcome using American Orthopaedic Foot and Ankle Society Clinical Rating System (AOFAS), return rate to sports, and period of return to the sports. Results: Preoperative size of lesion on MRI was 9.8 mm in sagittal view, and 6.0 mm in coronal view. Depth of the resected site in 3 months postoperative MRI was 3.1 mm. On one year postoperative MRI, the resected site was filled with cartilage like tissue, and the shape of restored site was good that mimicked the original shape (Figure 1). As for clinical outcome, AOFAS score was 65.4 points preoperatively, and it improved to 93.4 points 1 year postoperatively. In clinical outcomes of the athletes, all cases could return to sports. Average period to return sports was 5.6 months. Only in 1 case, mild pain during sports activity was remained. Preoperative AOFAS score of athletes was 71.4 points and it improved to 98.5 points postoperatively. Conclusion: According to this study, even if a symptom is mild, an early operation will be more likely to result in the early return to sports and good outcomes. In addition, these good outcomes and good congruency on 1 year postoperative MRI suggest that the restored cartilage like tissue is enough for the high activities. The cartilage is repaired with maintaining original shape of talus cartilage. And this method was effective for athletes and was able to get them return to sports with good outcome.